COMPARATIVE ANALYSIS OF LINEAR MEASUREMENTS BETWEEN IMPACTED AND ERUPTED MANDIBULAR THIRD MOLARS USING DIGITAL PANORAMIC RADIOGRAPHS - Surekha Waghanna; U.K.Gupta; Neelkant Patil; B.R.Adyanthaya; Rohit Sharma (Journal of Population Therapeutics and Clinical Pharmacology, 2023)
Background: Despite the widespread use of panoramic radiographs for assessing third molars, there remains a need for a more thorough understanding of the precise linear measurements associated with impacted versus erupted mandibular third molars. Linear measurements provide objective, quantifiable data that can help differentiate between impacted and erupted third molars. These measurements may include the angular position of the tooth, the root length, the proximity to critical structures like the inferior alveolar nerve, and the distance to adjacent teeth or bone. Comparing these linear measurements between impacted and erupted third molars can help identify subtle anatomical differences that may not be apparent through clinical examination alone. Material & Methods: All participants were exposed to digital panoramic radiograph with SIRONA ORTHOPHOS XG using exposing parameters of 68kvp, 11m PmA, and 18 second/Carestream 8000C. Out of these participants 520 mandibular third molar teeth were assessed and were divided into two following 2 groups : Group A consisted of 260 erupted mandibular third molar teeth and Group B consisted of 260 impacted mandibular third molar teeth. Pattern of impaction of mandibular third molar teeth was categorized according to Winter’s Classification into vertical, mesioangular, horizontal, distoangular, and others. Results: There is a significant difference in the mesiodistal width between impacted and erupted mandibular third molars. The impacted molars have a slightly larger MDW on average compared to erupted molars, with the difference being statistically significant. A significant difference is observed in the lower eruption space (LES-R) between impacted and erupted molars. Erupted molars have a larger average LES-R compared to impacted molars, indicating that less space is available in the impacted group, contributing to their impaction. Impact of Findings: The results indicate that erupted mandibular third molars generally have larger space measurements and higher space width ratios compared to impacted molars. These differences are statistically significant and suggest that space availability is a crucial factor in the eruption of mandibular third molars. Conclusion: The findings suggest that specific linear measurements, such as the distance between the impacted third molar and the second molar, can serve as predictive indicators for impaction and potential complications. Understanding these measurements allows for more accurate early diagnosis and better preoperative planning, improving patient outcomes.